Evaluation of Conversational Agents: Understanding Culture, Context and Environment in Emotion Detection - Teye, Martha T.; Missah, Yaw Marfo; Ahene, Emmanuel; Twum, Frimpong (IEEE Access, 2023)
An article published in IEEE Access, Vol. 10, 2022